La traducción de canciones en la prosa novelística: la canción del Ciego en Madame Bovary - Hernández-Guerrero, María José (Anales de Filología Francesa, 2024)
The inclusion of song lyrics in novelistic prose is a semiotic resource used in literature with some frequency. Through this operation, the song is deconstructed in literary discourse and transformed to acquire new meanings. This article examines the translation of these intertexts and the mechanisms used to bring out their musicality in the narrative, taking as a case study the song of the Blind Man that Gustave Flaubert inserts into Madame Bovary. This classic novel has been the subject of numerous translations into peninsular Spanish, which makes it possible to establish a representative corpus for analysing the way in which this musical intertext has been translated. The article describes the procedure adopted by Flaubert to introduce this song into the narrative diegesis and details the two mainmethods used by the translators to restore it and project its musicality into the writing:poetic translation and non-translation.
Keywords: Madame Bovary - Traducciones; Traducción literaria; Traducción de letras de canciones; Traducción de canciones; Intertexto musical